OPTIMALISASI PERAWATAN ALAT-ALAT KESELAMATAN SEBAGAI PENUNJANG KESELAMATAN AWAK KAPAL DI KN. BIMA SAKTI - Firdaus Sitepu (Politeknik Ilmu Pelayaran Semarang, 2017)
As for target of writing of this handing out is to know optimalization treatment of safety appliance as supporter safety of crew man in KN. Bima Sakti. Pursuant to the target, hence this handing out take title